Associations Between Adolescent Perceptions of Parental Interactions and Adolescent Sexual Behaviors - Fairley, Shakesha (Shai) (2016)
Sexual risk behaviors among U.S. adolescents is a major public health concern. Adolescents are contracting sexually transmitted diseases at alarming rates. The purpose of this research was to identify factors related to parent-child interactions that influence adolescent sexual behaviors. A combination of attachment theory and family systems theory was used to help explain how adolescent sexual choices (age of sexual debut, use of birth control, use of condoms, multiple sex partners in a 12-month period) are affected by the perceived quality of parent-child interactions (maternal/parental closeness, monitoring, communication, and involvement). Archival data from the U.S. Bureau of Labor Statistics National Longitudinal Survey of Child and Young Adult cohort 1979 (NLSY79) was used for this research. A sample of 11,504 adolescents aged 12 to 19 years, and their biological mothers who participated in the longitudinal survey, was drawn. Nonparametric analyses revealed significant differences in adolescent perceptions of maternal and paternal closeness and maternal perceptions of maternal and paternal closeness. Logistic regression analyses revealed that adolescents' perceptions of parental engagement (maternal and paternal closeness, monitoring, communication, and involvement) significantly affected their sexual choices (age of sexual debut, use of birth control, condoms, and multiple partners). The results of this study can be used to initiate positive social change by informing parents, program developers, and researchers. Developing strategies to guide parents and adolescents to develop positive perceptions of the interactions, closing the gap between adolescent and parental perceptions of interactions, will help reduce adolescent risky sexual behaviors, thereby benefiting the individuals, families, and the community